Genetics of age-related macular degeneration and Stargardt disease in South African populations - Baard, Johannes (Division of Human Genetics, 2016)
Background: The Retinal Degenerative Diseases (RDD) Research Group in the Division of Human Genetics at UCT has for the past 25 years been intensively investigating a range of RDD phenotypes. Two points of particular note have emerged regarding Macular Degenerations (MD) : (i) that more than 58% of juvenile MD, notably Stargardt Disease (STGD) , in Caucasian populations may have the underlying causative genetic defect identified , while only 1 1 % of the similar phenotype in indigenous African populations is resolved, and (ii) that the 'elderly' form of MD, i.e. age - related macular degeneration (AMD) has a remarkably lower incidence in the indigenous African population when compared to any other population group, and most notably the Caucasian (or European - derived) population /s . This study investigates the genetic factors underlying macular degeneration (MD) in our study cohort comprising various South African ethnolinguistic groups with particular focus on disease in juvenile and elderly indigenous Africans. Materials and Methods: For the STGD part of the study, sequencing of the entire ABCA4 coding and splice region (comprising 50 amplicons) was performed in three African STGD patients who were representative of three common haplotypes identified within the larger cohort of 36 patients . Pathogenicity predictive software, PON - P and Human Splice Finder (HSF), were used for in silico data analysis. For the AMD subset: Available local indigenous southern African population - based genome - wide S ingle Nucleotide Polymorphism (SNP) chip (Affymetrix SNP6) data was used to identify SNPs within known AMD candidate genes in which allele frequencies were significantly different (i.e. 10 fold) between Caucasians and indigenous southern Africans. Nine SNPs occurring at higher frequencies within Africans compared to Caucasian controls were genotyped by SNaPshot PCR within a multi - ethnic AMD SA cohort. Minor allele frequencies (MAF) were compared using SHEsis. Results: Sequencing of ABCA 4 in three African STGD patients produced 39 unique variants, out of which only one, (V643M), was deemed pathogenic. HSF predicted 22 of these non - exonic variants to be 'possibly pathogenic', confounding analysis. No variants segregated with the common haplotypes. Regarding the AMD cohort, eight SNPs in candidate AMD genes showed a decreased MAF in African AMD cases compared to controls, two of which (rs9621622 in TIMP3 and rs17110714 in ABCA4 ), were statistically significant ( p values of 9.95 x 10 - 4 and 1.04 x 10 - 2 , respectively). Discussion and Conclusion: Although a number of variants were identified in the coding region of three haplotype - representative STGD subjects, only one variant proved pathogenic but did not co - segregate with the haplotype in the rest of the samples. It is possible that variants in regulatory regions not captured by the exonic screening might be involved, or that another gene may be imp licated in the 'STGD - like' phenotype in the indigenous African subjects. In the second part of the study, the investigation of the African AMD cohort suggested that SNPs in TIMP3 and ABCA4 are associated with a decreased susceptibility, and may therefore plausibly be protective for AMD in indigenous Africans. Overall, however, this should be considered only a pilot study of macular degeneration in the indigenous African population, providing leads to larger scale studies of this group of disorders in this population group.